Women in Medieval Society - Stuard, Susan Mosher; Bolton, Brenda (Middle Ages., 1976)
Early medieval women exercised public roles, rights, and responsibilities. Women contributed through their labor to the welfare of the community. Women played an important part in public affairs. They practiced birth control through abortion and infanticide. Women committed crimes and were indicted. They owned property and administered estates. The drive toward economic growth and expansion abroad rested on the capacity of women to staff and manage economic endeavors at home. In the later Middle Ages, the social position of women altered significantly, and the reasons why the role of women in society tended to become more restrictive are examined in these essays.